(untitled) (Agora for Physical Education and Sport, 2021)
The following article aims to investigate the Curricular Design of Physical Education for the Preschool Level during the last civic-military dictatorship in Argentina. This document was issued in 1982 by the Secretary of Education of the Municipality of the City of Buenos Aires. To do this, we analyze the components of the curricular document, focusing on the objectives of the first educational link and its foundation. In turn, a relationship is made with the general objectives of the educational system of the period. As preliminary results, we see that a technical and personalistic pedagogy of Physical Education is manifested, from which the task of teaching motor tasks is attributed under a psychomotor and developmental paradigm. In addition, we find influences from German Gymnastics. However, there are inconsistencies between the foundations of Physical Education and the proposed objectives and activities, which are far from the concepts of child autonomy and creativity.